COVID-19 vaccine hesitancy among Nigerian youths: Case study of students in Southwestern Nigeria - David B Olawade; Ojima Z Wada; Aderonke Odetayo; Oluwabusayomi O Akeju; Fiyinfoluwa T Asaolu; Grace O Owojori (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND AND AIM: Vaccination has been appraised to be one of the most significant public health achievements in human history. However, in countries like Nigeria, vaccine hesitancy is a public health challenge that has consistently forestalled concerted efforts made by health authorities to curb the spread of communicable diseases such as COVID-19. To improve COVID-19 vaccine acceptance via targeted interventions, it is imperative to examine the public's perception. Thus, this study aims to evaluate vaccine hesitancy among university students in Southwestern Nigeria. MATERIALS AND METHODS: The study utilized a descriptive cross-sectional design. A self-administered questionnaire was administered to a total of 366 respondents who were recruited using the convenience sampling technique and snowball approach. Data were entered and analyzed using SPSS. RESULTS: The majority of the respondents were over 18 years (88%) and were between their first and third years (81%). Over a tenth of the respondents reported having at least a loved one that had tested positive for the virus, while only 88% believed the virus is real. Furthermore, only 17% of the students had a positive attitude toward the vaccine. Although 90% of the respondents were aware of the administration of COVID-19 vaccine in Nigeria, only around a quarter were willing to take the vaccine, while 5.5% had been vaccinated. The major reasons for COVID-19 vaccine hesitancy highlighted by the respondents were concerns about vaccine side effects (21.3%), lack of trust in the authorities (26.5%), vaccine efficacy (13.1%), and diverse mystical possibilities (39.1%). CONCLUSION: The results indicate that a significant communication gap exists between the respondents and local health authorities. To enhance the acceptance of COVID-19 vaccines, extensive and targeted health promotion campaigns are required to allay specific concerns raised by the public.